Optimal Sca-1-based procedure for purifying mouse adipose-derived mesenchymal stem cells with enhanced proliferative and differentiation potential - Xingyu Tao; Jialian Wang; Yuan Yan; Peifeng Cheng; Bin Liu; Huimin Du; Bailin Niu; Bailin Niu (Frontiers in Cell and Developmental Biology)
IntroductionAdipose-derived mesenchymal stem cells (ADSCs) are promising candidates for mesenchymal stem cell (MSC) therapy due to their ease of isolation from the stromal vascular fraction (SVF) of adipose tissue. However, traditional isolation methods often result in mouse ADSCs with low purity and significant heterogeneity contributing to inconsistencies in results from preclinical and clinical studies. This is partly attributed to the lack of consensus on their surface markers.MethodsThis study compared three purification methods for isolating mouse ADSCs based on Sca-1 positivity—direct adherence (ADSC-A), magnetic cell sorting followed by adherence (ADSC-M), and adherence to the third generation followed by magnetic cell sorting (ADSC-AM). Third-generation ADSCs were evaluated for proliferative activity, differentiation potential, and functional enrichment using proliferation assays, trilineage differentiation assays, and RNA sequencing. Flow cytometry was employed to assess Sca-1 positivity and the expression of positive (CD44, CD90, CD29) and negative markers (CD31, CD45) in the fourth-generation ADSCs.ResultsAmong the three methods, ADSC-AM exhibited superior properties, including uniform morphology, enhanced proliferation, and over 95% expression of Sca-1 and CD29. While all methods supported trilineage differentiation, ADSC-AM demonstrated enhanced adipogenesis. Furthermore, RNA sequencing and pathway enrichment analysis revealed that ADSC-AM possessed unique potential in angiogenesis and immune regulation.DiscussionThese findings suggest that the ADSC-AM method offers a simple and reproducible approach for obtaining high-purity mouse ADSCs with better functional properties and provide a fundamental reference for understanding mouse ADSCs surface marker profiles.